"Patriarchal reset" in the asia pacific during COVID-19: the impacts on women's security and rights. Issue 3 (4th May 2023) - Johnston, Melissa; Davies, Sara E.; True, Jacqui; Riveros-Morales, Yolanda
Abstract: COVID-19 has disrupted social, economic and political life across the Asia Pacific region, with particularly deleterious impacts on women. Rather than equitably affecting all, COVID-19 has brought about a "patriarchal reset", exacerbating women's health and care labour burdens and heightening the physical violence against women and other threats to women's human rights. This paper examines global health governance in the region from a feminist political economy perspective. We ask how has the pandemic and associated lockdowns affected women's safety and access to economic resources and services on the one hand, and 'women, peace and security' (WPS) practitioners' capacity to safeguard women's rights in fragile settings on the other hand? We examine the gendered impacts of COVID-19 based on two surveys of WPS practitioners during 2020. Significant rises in domestic and gender-based violence, reduced access to reproductive health services, and increased income insecurity were all perceived and/or experienced during COVID-19 restrictions. WPS practitioners delivered services to mitigate these effects of COVID-19 despite overall less funding than before COVID-19. With the benefit of primary data, we explore how a more radical approach is needed to understand and transform gender relations in light of gender-based violence and depletion of women's labour.